PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA YANG DIRUMAHKAN TERKAIT REMUNERASI DALAM MASA PANDEMI COVID-19 - Dhitania Annisa (Fakultas Hukum UM Tapanuli Selatan, 2021)
Due to the Covid-19 pandemic, many companies have had an impact on government regulations as well as health reasons for carrying out work activities from home, and have an impact on workers who are sent home, this policy has an impact on providing remuneration for workers. The research aims to look at legal protection for workers who are sent home regarding remuneration during the Covid-19 pandemic. This is the background of the problem regarding how legal protection for workers who are sent home related to remuneration during the Covid-19 pandemic based on the appropriate legislation and dependents for companies that do not provide remuneration for workers who were sent home during the Covid-19 pandemic. The research reveals that regarding wage protection and protection for workers in the workplace, employers can provide a suspension of wage payments, in which case the employer is unable to pay wages in accordance with the wage regulations, which must first negotiate with workers first. The postponement of the payment of the minimum wage made by the employer against the worker does not eliminate the obligation of the employer to pay the difference in the minimum wage during the period of suspension.